An Empirical Investigation into the Determinants of Foreign Exchange Hedging and its Exposures for UK Firms. - Ryan, Katrina (2017)
This paper empirically examines foreign exchange (FX) hedging by UK firms to provide evidence on the determinants of a firm’s decision to hedge FX. This study provides a unique insight into the topic by employing a comparative study on the determinants of FX hedging, transaction exposure hedging and translation exposure hedging. Through a series of univariate and multivariate tests, firm size, foreign exposure and leverage are found to be the most powerful explanatory variables in a firm’s decision to hedge FX and its exposures. Moreover, an investigation into the definition of FX hedgers indicates that a more inclusive definition provides more significant, yet similar results.